Analisis Peran Baznas Dalam Melindungi Kelompok Rentan Dan Mengurangi Kesenjangan (Studi Kasus Baznas Kabupaten Mojokerto) - Shinta Lintang Nurillah; Ach. Yasin (ITB AAS INDONESIA Surakarta, 2021)
Inequality is one of the problems in Indonesia that cannot be immediately resolved. This condition is exacerbated by the lifestyle of the people who tend to be consumerism, control of the economic sector which is only centered on a group of people and the limitations of the state in realizing its obligations as mandated in the 1945 Constitution. So an institution is needed to help accelerate government programs in alleviating vulnerable groups through programs such as empowerment. and economic assistance. The approach used in this research is descriptive qualitative with a case study method at the National Zakat Agency (BAZNAS) in Mojokerto Regency. How to collect data using interviews, observation, and documentation. Based on this research, it was found that in protecting Vulnerable Groups the efforts made by BAZNAS Mojokerto Regency have so far been good, proven by the criteria for receiving BAZNAS assistance such as KKM, Mustahiq Consumptive, Mustahiq Criterion B, Mustahiq Criterion A. Meanwhile, in reducing gaps in the region Mojokerto BAZNAS Regency cannot be said to be able to reduce the current gap.